Epidemiology of international match injuries in Scottish rugby: A prospective cohort study - Bailey, S. J.; Martindale, R.; Engebretsen, L.; Robson, J. P.; Palmer, D. (International Journal of Sports Medicine, 2023)
Fifteen-a-side rugby union ("rugby") is a full-contact sport played separately by men and women, with large injury incidences reported previously. Context specific injury surveillance fulfils governing bodies` duty of care to understand risks to player welfare, yet no contemporary match injury epidemiology studies exist for international players in Scotland. The current study therefore aimed to describe the incidence, severity, burden and nature of match injuries sustained by Scotland`s men`s and women`s national teams. A prospective cohort study of injuries recorded in matches across the 2017/18 and 2018/19 seasons was undertaken, with injury and exposure definitions in line with the international consensus for injury surveillance in rugby. Injury incidence was 120.0 (men) and 166.7/1,000 player match hours (women), injury severity was 12.0 (median) and 31.2 days (mean) for men, and 11.0 (median) and 30.2 days (mean) for women. Injury burden was 3,745 (men) and 5,040 days absence/1,000 player match hours (women). Concussion was the most common specific injury for men (22.5/1,000 hours) and women (26.7/1,000 hours). No statistical differences were found for incidence or severity measures between sexes. Injury incidence was greater than recent Rugby World Cup studies. High incidences of concussion reinforces the need for prevention strategies targeting this injury.